The COVID-19 chronicles of Malaysia the tsunami 1 Jan 2021 - 31 July 2021 : The 4th Chronicle (National Institutes of Health, 2021)
It compiles information obtained from government documents, open data and newspaper clippings on the COVID-19 pandemic in Malaysia. The book provides a chronology of public health strategies taken in the country. This offers other countries a way to understand Malaysia's health system strategies and learn from them.